The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.neuroscience.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal alkalization and dysfunction in human fibroblasts with the Alzheimer’s disease-linked presenilin 1 A246E mutation can be reversed with cAMP

Abstract: Mutation in presenilin 1 (PS1) is one of the leading causes of familial Alzheimer’s disease (fAD). PS1 mutation exacerbates the autophagic and lysosomal pathology in AD patients, leading to accumulation of partially degraded material in bloated lysosomes and autophagosomes – a pathology that bears some resemblance to other diseases characterized by elevated lysosomal pH, like age-related macular degeneration. In this study, we examined the effect of the PS1-fAD mutation A246E on lysosomal pH and lysosomal func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 74 publications
6
127
0
Order By: Relevance
“…Moreover, stable transfection of PS1 into PS1/2 DKO cells reverses these features and restores V0a1 subunit glycosylation, lysosomal acidification and autophagic clearance (Lee et al, 2010). Importantly, additional studies have also demonstrated impaired vATPase V0a1 subunit maturation and endolysosomal acidification in multiple models, including PS1 ablated cells or mutant PS1 models (Avrahami et al, 2013; Coffey et al, 2014; Dobrowolski et al, 2012; Torres et al, 2012; Wolfe et al, 2013), underscoring that the acidification defect induced by PS1 loss of function is generalisable across various cell types. In one study, PS1 and vATPase V0a1 subunit were reported to have no role in lysosomal pH regulation (Coen et al, 2012) and differences between methods and cell culture conditions might explain some discrepancies between this study and our studies.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, stable transfection of PS1 into PS1/2 DKO cells reverses these features and restores V0a1 subunit glycosylation, lysosomal acidification and autophagic clearance (Lee et al, 2010). Importantly, additional studies have also demonstrated impaired vATPase V0a1 subunit maturation and endolysosomal acidification in multiple models, including PS1 ablated cells or mutant PS1 models (Avrahami et al, 2013; Coffey et al, 2014; Dobrowolski et al, 2012; Torres et al, 2012; Wolfe et al, 2013), underscoring that the acidification defect induced by PS1 loss of function is generalisable across various cell types. In one study, PS1 and vATPase V0a1 subunit were reported to have no role in lysosomal pH regulation (Coen et al, 2012) and differences between methods and cell culture conditions might explain some discrepancies between this study and our studies.…”
Section: Discussionmentioning
confidence: 98%
“…Rescue of lysosomal defects can restore autophagic activity. For example cAMP treatment decreased lysosomal pH in patient fibroblasts (16). Further, deletion of cystatin B (an inhibitor of lysosomal cysteine proteases) in an AD mouse model enhanced defective lysosomal turnover, promoted Aβ clearance, and improved mouse cognitive performance (17).…”
Section: G2019smentioning
confidence: 99%
“…Sequence-specific primers for MUC5AC and ATG5 were used as previously published. 11,63 Gene expression was normalized to OAZ1. 64 …”
Section: Quantitative Pcrmentioning
confidence: 99%